2023
DOI: 10.1093/humupd/dmad002
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive ability in survivors of childhood, adolescent, and young adult Hodgkin lymphoma: a review

Abstract: BACKGROUND Owing to a growing number of young and adolescent Hodgkin lymphoma (HL) survivors, awareness of (long-term) adverse effects of anticancer treatment increases. The risk of impaired reproductive ability is of great concern given its impact on quality of life. There is currently no review available on fertility after childhood HL treatment. OBJECTIVE AND RATIONALE The aim of this narrative review was to summarize exis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 168 publications
0
14
0
Order By: Relevance
“…Furthermore, this difference also may result from various ART approaches. Some studies have also reported decreased sperm counts and anti-Müllerian hormone concentration among lymphoma patients prior to treatment, suggesting that spermatogenesis was also affected by the disease ( Pallotti et al , 2021 ; Drechsel et al , 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, this difference also may result from various ART approaches. Some studies have also reported decreased sperm counts and anti-Müllerian hormone concentration among lymphoma patients prior to treatment, suggesting that spermatogenesis was also affected by the disease ( Pallotti et al , 2021 ; Drechsel et al , 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…Infertility risks are primarily associated with exposure to higher cumulative doses of alkylating agents, especially procarbazine (with BEACOPP), infradiaphragmatic RT, and after ASCT. 69 Although novel therapies including Bv and immune checkpoint inhibitors improve PFS and OS and the potential to decrease exposure to conventional chemotherapy and RT, these agents are associated with unique adverse effects. Lower incidence of severe peripheral neuropathy and infection associated with Bv have been noted in AYAs compared with older adults.…”
Section: Toxicity Concernsmentioning
confidence: 99%
“…Infertility risks are primarily associated with exposure to higher cumulative doses of alkylating agents, especially procarbazine (with BEACOPP), infradiaphragmatic RT, and after ASCT. 69…”
Section: Toxicity Concernsmentioning
confidence: 99%
“…There is a peak in cHL incidence in adolescents aged 15–19 years, accounting for 6%–7% of all childhood malignancies 25 . Nowadays after chemotherapy or chemo‐RT, in this setting, the 5‐year OS overcomes the 90% 26–28 but the post‐actinic long‐term toxicities in the survivors are not negligible (i.e., second malignancies, cardiovascular disease, thyroid dysfunction and infertility) 29,30 . The treatment protocols, that are different from the adult one, 31 are chosen not only on the basis of the risk categories (including tumor stage, bulk of disease and the presence of B symptoms) and the analysis of the ad‐interim response by a positron emission tomography and/or measuring metabolic tumor volume 32 .…”
Section: What Have We Understood So Far? Clinical Indicationmentioning
confidence: 99%